Emotion Residue in Neutral Faces: Implications for Impression Formation. Issue 4 (May 2021) - Albohn, Daniel N.; Adams, Reginald B.
Despite the prevalent use of neutral faces in expression research, the term neutral still remains ill-defined and understudied. A general assumption is that one's overt attempt to pose a nonexpressive face results in a neutral display, one devoid of any expressive information. Ample research has demonstrated that nonexpressive faces do convey meaning, however, through emotion-resembling appearance. Here, we examined whether prior expressive information lingers on a face, in the form of emotion residue, and whether despite overt attempts to display a neutral face, these subtle emotion cues influence trait impressions. Across three studies, we found that explicit attempts at posing neutral displays retained emotion residue from a prior expression. This residue in turn significantly impacted the impressions formed of these otherwise "neutral" displays. We discuss implications of this work for better understanding how accurate impressions are derived from the so-called neutral faces and underscore theoretical and methodological considerations for future research.